Standardization of TLC Methods for Identification of Carcino-genic Aryl Amines in Colored Textile and Leather Products - Singh, A.P.; Kumar, R. (Asian Journal of Chemistry, 2010)
Many attempt have been made to detect carcinogenic aryl amines in colored textile and leather products by TLC. But better resolution was the problem among mixtures of such amines. A chemical approach is shown to solve the resolution problems. For the good resolution, a mixture of ethyl acetate and n-hexane was used as a mobile phase. The whole procedure was standardized with standard of carcinogenic aryl amines and tested with samples of coloured textile and leather products. Resolution of amines was also observed under HPTLC scanner.